2013
DOI: 10.1158/0008-5472.can-12-2501
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Deregulated Spliceosome Core Machinery in Cancer Cells Triggers mTOR Blockade and Autophagy

Abstract: The spliceosome is a large ribonucleoprotein complex that guides pre-mRNA splicing in eukaryotic cells. Here, we determine whether the spliceosome could constitute an attractive therapeutic target in cancer. Analysis of gene expression arrays from lung, breast, and ovarian cancers datasets revealed that several genes encoding components of the core spliceosome composed of a heteroheptameric Sm complex were overexpressed in malignant disease as compared with benign lesions and could also define a subset of high… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
87
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 39 publications
7
87
0
Order By: Relevance
“…Currently, the common housekeeping genes include small nuclear/nucleolar RNAs such as RNU44, RNU48 and RNU6-1, also more commonly known as U6. The spliceosome complex, which catalyzes pre-mRNA splicing, and in which U6 is a key functional component, is frequently deregulated in a wide variety of cancers [30]. Consistent with this and with our findings, it has been shown that serum RNU6-1 levels are differentially expressed in serum from individuals with breast cancer compared to healthy controls [31].…”
Section: Discussionsupporting
confidence: 91%
“…Currently, the common housekeeping genes include small nuclear/nucleolar RNAs such as RNU44, RNU48 and RNU6-1, also more commonly known as U6. The spliceosome complex, which catalyzes pre-mRNA splicing, and in which U6 is a key functional component, is frequently deregulated in a wide variety of cancers [30]. Consistent with this and with our findings, it has been shown that serum RNU6-1 levels are differentially expressed in serum from individuals with breast cancer compared to healthy controls [31].…”
Section: Discussionsupporting
confidence: 91%
“…We identified most of the spliceosomal proteins that previously have been shown to be hyperexpressed in ovarian cancer cells (37) (supplemental Table S5). This result was of special interest because Quidville et al demonstrated that some spliceosomal components hyperexpressed in cancer cells participate in the regulation of the PI3K/Akt/mTOR pathway, which is often disturbed in ovarian cancer (38). Thus, spliceosome components are attractive targets for anticancer therapy.…”
Section: Discussionmentioning
confidence: 97%
“…Overexpression of Sm domain spliceosome proteins has been found in a number of malignancies and defines a subset of cancers with aggressive features (Quidville et al 2013). A number of studies have identified frequent and recurrent somatic mutations in spliceosome machinery components such as SF3B1, ZRSR2, U2AF1, and SRSF2 in multiple cancer types.…”
Section: Discussionmentioning
confidence: 99%